Importance of diet in polycystic ovary syndrome - Papović, Nevena; Djermanović, Mirjana (Archives of Pharmacy, 2022)
Polycystic ovary syndrome (PCOS) is one of the most common metabolic disorders in women of fertile age. The first step in the treatment of this syndrome is a change in life habits, which in the first place refers to eating habits, where food choice plays a key role. The aim of this study was to determine how many women with PCOS have a balanced diet that is important in the treatment of PCOS. A group of 20 fertile women ranging in age from 15 to 40 years was taken as the test sample. All participants filled out a questionnaire that talks about the impact of diet on the course of the disease and their experiences with it. Part of the questionnaire was related to demographic data and other part was specific to the diet itself. Also, some of the questions was with the offered answers and also some of them was open type questions. A group of 20 fertile women was analyzed and some of them had insulin resistance (especially those who were overweight) and were not physically active. Diabetes type was not present in the respondents. The obtained results instructed us that it is necessary to go towards the correction of diet and life habits in order to improve the metabolism and hormonal state of the woman’s body, because diet has a positive overall effect on the course of the disease in women suffering from PCOS.